”You Never Know What Happens Next” – Young Adult Service Users’ Experience with Mental Health Care and Treatment through One Year - Marian Ådnanes; Sissel Steihaug (International Journal of Integrated Care, 2016)
Fragmented services are a well-known problem in the mental health sector. Mental health service users’ experiences of treatment and care can provide knowledge for developing more user-oriented continuity of care. We followed nine young adults with mental health illnesses and complex needs, conducting four interviews with each informant in the course of a year. The aim was to capture their experiences and views about treatment and care, focusing on (dis)continuities and episodes occurring through that year. The users’ experiences were affected by shifts and transitions between institutions, units and practitioners while their need was predictability and stability. A good and stable patient-provider relationship was considered highly useful but difficult to establish. The participants had a strong desire for explanation, adequate treatment and progress, but very different perceptions of the usefulness of diagnoses. Some felt rejected when they tried to tell the therapist about their trauma. Lack of user-involvement characterized many of the participants’ stories while they desired to become more engaged and included in important decisions concerning treatment and medication. The participants’ experiences stand in contrast to key policy goals of coherent mental health services. The article discusses what may explain the gap between policy and reality, and how continuity of care may be improved.